2019
DOI: 10.1038/s41598-019-41202-4
|View full text |Cite|
|
Sign up to set email alerts
|

Moderate Nucleoporin 133 deficiency leads to glomerular damage in zebrafish

Abstract: Although structural nuclear pore proteins (nucleoporins) are seemingly required in every cell type to assemble a functional nuclear transport machinery, mutations or deregulation of a subset of them have been associated with specific human hereditary diseases. In particular, previous genetic studies of patients with nephrotic syndrome identified mutations in Nup107 that impaired the expression or the localization of its direct partner at nuclear pores, Nup133. In the present study, we characterized the zebrafi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…Morphant zebrafish with nup107 knock-down [87] as well as CRISPR/Cas9mediated in-frame mutations in nup107 [90] mimicked the allelic effects seen in human patients and caused hypoplastic glomerulus structures and pathological podocyte foot processes. Morpholino-mediated depletion of nup133 in zebrafish likewise led to the formation of kidney cysts, moderate foot process effacement and proteinuria, while the overall kidney development was not impaired [95]. Consistent with the results in zebrafish models, morpholino-mediated knock-down of nup107, nup85, or nup133 in Xenopus caused defects in glomerular structure and function [90].…”
Section: Nephrotic Syndromessupporting
confidence: 74%
“…Morphant zebrafish with nup107 knock-down [87] as well as CRISPR/Cas9mediated in-frame mutations in nup107 [90] mimicked the allelic effects seen in human patients and caused hypoplastic glomerulus structures and pathological podocyte foot processes. Morpholino-mediated depletion of nup133 in zebrafish likewise led to the formation of kidney cysts, moderate foot process effacement and proteinuria, while the overall kidney development was not impaired [95]. Consistent with the results in zebrafish models, morpholino-mediated knock-down of nup107, nup85, or nup133 in Xenopus caused defects in glomerular structure and function [90].…”
Section: Nephrotic Syndromessupporting
confidence: 74%
“…4). In addition to the labeled podocytes and parietal epithelial cells in these transgenics, we performed the angiography using bovine serum albumin (BSA) conjugated with AlexaFluor555 to mark the endothelial cells of glomerular capillaries as previously described [59]. We visualized glomeruli development and its vascularization throughout five different stages; at 30, 48, 52, 72, 120 hpf.…”
Section: Development and Vascularization Of Glomerulus In The Zebrafi...mentioning
confidence: 99%
“…Studies on Nup133 and Nup107, both members of the same scaffold subcomplex, have provided some insights into the role of Nups in kidney physiology. Spatiotemporal analysis of Nup133 expression during zebrafish development has shown that, by 5 days post-fertilization, this Nup is mainly expressed in liver, but also in pronephric proximal tubules and the glomerulus at lower levels (Cianciolo Cosentino et al, 2019). Morpholinomediated knockdown of Nup133 results in glomerular expansion, formation of kidney cysts, and liver misplacement.…”
Section: Kidneymentioning
confidence: 99%